(3GdLhGgQ GdKejfI aj ePgH YGde GdeOjfIs - (3GHf fRGQ GdLPGeis; (3CHh eMeO YHO Gddg Hf eMeO Hf fLe Hf TGS GdeUQj (B( (3Hf fRGQ GdLPGej(B)(3,J (B610 (3g` s
(3ChdgG (B:s
(3XGgQgG ChYO GdePgH Ydi bhdjf fai GdfbV eWdbkG hGdJaUjd Ydi KdGK WQb s
(3BNQgG (B:s
(3Ydi ZQjeI GKfJjf Je GdLRA GdChd ef YbO GdLhGgQ GdKejfI aj ePgH YGde GdeOjfI jJdhg aj GLRA GdKGfj GdHGH GdMGOj YTQ aj UdGI GdNha s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B613s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdeGdcjs